If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.07y + -1.6 = 2.1y + 1.2 Reorder the terms: -1.6 + -0.07y = 2.1y + 1.2 Reorder the terms: -1.6 + -0.07y = 1.2 + 2.1y Solving -1.6 + -0.07y = 1.2 + 2.1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2.1y' to each side of the equation. -1.6 + -0.07y + -2.1y = 1.2 + 2.1y + -2.1y Combine like terms: -0.07y + -2.1y = -2.17y -1.6 + -2.17y = 1.2 + 2.1y + -2.1y Combine like terms: 2.1y + -2.1y = 0.0 -1.6 + -2.17y = 1.2 + 0.0 -1.6 + -2.17y = 1.2 Add '1.6' to each side of the equation. -1.6 + 1.6 + -2.17y = 1.2 + 1.6 Combine like terms: -1.6 + 1.6 = 0.0 0.0 + -2.17y = 1.2 + 1.6 -2.17y = 1.2 + 1.6 Combine like terms: 1.2 + 1.6 = 2.8 -2.17y = 2.8 Divide each side by '-2.17'. y = -1.290322581 Simplifying y = -1.290322581
| 2x+3y=5x-2y+7 | | Kx(X-6)=2 | | .13x+X=20.34 | | 2.5r=120 | | 7.7a+11=72.6 | | 7+55x=33x+19 | | 5+5=2 | | (.2y)*y=.45 | | -8h+2h-10=-28 | | 3.5(-83x-3)=3.7(7x-30) | | 2x=3x-23 | | y=-16x^2+12x+0.2 | | x+29=51 | | y-5=-9(x-4) | | X^3y^2+3X^2y-28X=0 | | -0.72E-4= | | 12x^2+3x+8x+2= | | 3x+1+x+4=9-x | | 12+8x=5x+3 | | 8m^2-11m-10=0 | | 76=7+2x | | 69=23x | | 2(z-3)=4(3+x) | | -90+3=a | | -90+3= | | -(x-4)=3 | | (5+y)(3y+7)=0 | | 6-3c=6-3c | | 8(x+4)=6x+80 | | 3k-10=11 | | 2*x+15= | | 5*243= |